The Oceans’ Biological Carbon Pumps: Framework for a Research Observational Community Approach - Claustre, Hervé; Legendre, Louis; Boyd, Philip W.; Levy, Marina (Frontiers in Marine Science, 2021)
A recent paradigm explains that the downward pumping of biogenic carbon in the ocean is performed by the combined action of six different biological carbon pumps (BCPs): the Biological Gravitational Pump, the physically-driven pumps (Mixed Layer Pump, Eddy Subduction Pump and Large-scale Subduction Pump), and the animal-driven pumps (diurnal and seasonal vertical migrations of zooplankton and larger animals). Here, we propose a research community approach to implement the new paradigm through the integrated study of these BCPs in the World Ocean. The framework to investigate the BCPs combines measurements from different observational platforms, i.e. oceanographic ships, satellites, moorings, and robots (gliders, floats, and robotic surface vehicles such as wavegliders and saildrones). We describe the following aspects of the proposed research framework: variables and processes to be measured in both the euphotic and twilight zones for the different BCPs; spatial and temporal scales of occurrence of the various BCPs; selection of key regions for integrated studies of the BCPs; multi-platform observational strategies; and upscaling of results from regional observations to the global ocean using deterministic models combined with data assimilation and machine learning to make the most of the wealth of unique measurements. The proposed approach has the potential not only to bring together a large multidisciplinary community of researchers, but also to usher the community towards a new era of discoveries in ocean sciences.